Features of the growth of English oak forest plantations established with different planting materials in Kharkiv Forest Research Station - Даниленко, О. М.; Румянцев, М. Г.; Тарнопільський, П. Б.; Лук’янець, В. А. (Forestry and Forest Melioration, 2024)
Introduction Artificial reforestation does not always enhance the quality and reproductive success of biologically sustainable and productive forest stands. One approach to addressing this challenge is the establishment of artificial plantations using containerised seedlings, which have several advantages over bare-root seedlings. Consequently, the use of containerised seedlings is being increasingly integrated into silvicultural practices. The study aimed to compare the growth performance, survivability, and preservation rates of five-year-old English oak plantations established using containerised seedlings grown on substrates of different compositions and those established with bare-root seedlings. Materials and Methods The research was conducted on a permanent multivariate research site within the Pivdenne forestry of the Kharkiv Forest Research Station in fresh maple-lime oak forest. The plantations were established in July 2016 using containerised seedlings cultivated on substrates composed of medium loamy soil, peat, and fresh sawdust in different proportions. The survivability, preservation, and growth parameters of the experimental plantations were compared to those of plantations of the same age established with bare-root seedlings. Data from measurements and observations of experimental plantations were analysed using descriptive statistics in MS Excel. The statistical significance of differences between control and experimental variants was assessed at the 5% significance level. Results The composition of the substrate used for containerised oak seedlings significantly influenced their biometric parameters. Seedlings grown on a substrate containing medium loamy soil and peat in 3:1 or 2:1 ratio (by volume) exhibited the greatest height and root collar diameter. This substrate composition is recommended for growing English oak seedlings in agrofibre containers at the Kharkiv Forest Research Station. Plantations established with containerised seedlings exhibited higher survivability (91–98% vs. 85%) and preservation rates (83–89% vs. 78%) compared to those established with bare-root seedlings. At five years of age, all plantation variants established with containerised seedlings demonstrated superior growth parameters compared to those established with bare-root seedlings, with differences of up to 32% in height, 53% in diameter, and 33% in height increment. The highest growth parameters at five years were recorded for English oak plants in the ‘Soil + peat (3:1)’ variant, while the lowest values were observed in the ‘Soil + sawdust (2:1)’ variant. Conclusions The findings of the study should be used in future revisions to the regulatory document “On the approval of the Instruction on Design, Technical Acceptance, Accounting, and Quality Assessment of Forestry Objects”, specifically regarding normative survivability and quality indicators for plantations established with containerised seedlings when transplanted to forested areas, including the density of the main species. 2 Figs., 2 Tables, 11 Refs.